Quantification of Gardnerella vaginalis, Atopobium vaginae and Lactobacillus spp. in bacterial vaginosis - Nedzib Numanovic; Snezana Ribis; Jelena Cukic; Dane Nenadic; Aleksandar Zivanovic; Predrag Sazdanovic; Violeta Ninkovic; Dejan Baskic (Journal of Infection in Developing Countries)
Introduction: The aim of the study was to investigate prevalence of bacteria most frequently associated with bacterial vaginosis using Amsel’s criteria as well as to quantify these bacteria by real-time PCR and to explore the difference in their quantity between healthy and bacterial vaginosis samples.